Gifford Lectures (1997/98): Genes, genesis and God, a series of ten lectures by Professor Holmes Rolston - Gifford Lectures Committee, Edinburgh, author; The University of Edinburgh, publisher (Colorado State University. Libraries, 1997)
Flyer of the Gifford Lectures given by Dr. Rolston at the University of Edinburgh, Academic Year 1997-1998, in November 1997.
Keywords: Colorado State University; university distinguished professor; philosophy professor; Gifford Lectures; Rolston, Holmes, 1932-2025